JOB MISMATCHES AMONG INDIGENOUS WORKERS IN CANADA:: FINDINGS FROM PIAAC DATA (Canadian Journal of Native Studies, 2026)
Using data from the Programme for the International Assessmentof Adult Competencies (PIAAC), this study examinedskill-job mismatches among Indigenous workers in Canada.Skill mismatches (over-skilled or under-skilled conditions)were based on direct measures of skill competencies in numeracyand literacy provided by PIAAC data.On average, Indigenous workers were more likely to be under-skilled, and less likely to be over-skilled, than their non-Indigenouscounterparts. These findings may be explained bythe fact that the level of education and the skill scores of Indigenousworkers were significantly lower than those of non-Indigenousworkers. When education was controlled, however,there were no differences in being under- or over-skilled in literacybetween Indigenous and non-Indigenous workers. Thatis, education level played an important role in determiningskill levels as well as job mismatches.Certain job-related conditions were associated with the likelihoodof job mismatch among Indigenous workers. Comparedto full-time workers, part-time Indigenous workerswere more likely to be over-skilled; compared with employees,self-employed Indigenous workers were less likely to beunder-skilled; and a higher level of skill-job mismatches werefound among Indigenous workers who majored in the field ofscience, technology, engineering, and mathematics (STEM) intheir post-secondary education than their non-STEM counterparts.